Short‐Chain Fatty Acid Butyrate Is an Inotropic Agent With Vasorelaxant and Cardioprotective Properties - Jacob Marthinsen Seefeldt; Casper Homilius; Jakob Hansen; Thomas Ravn Lassen; Nichlas Riise Jespersen; Rebekka Vibjerg Jensen; Ebbe Boedtkjer; Hans Erik Bøtker; Roni Nielsen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background The heart can metabolize the microbiota‐derived short‐chain fatty acid butyrate. Butyrate may have beneficial effects in heart failure, but the underlying mechanisms are unknown. We tested the hypothesis that butyrate elevates cardiac output by mechanisms involving direct stimulation of cardiac contractility and vasorelaxation in rats. Methods and Results We examined the effects of butyrate on (1) in vivo hemodynamics using parallel echocardiographic and invasive blood pressure measurements, (2) isolated perfused hearts in Langendorff systems under physiological conditions and after ischemia and reperfusion, and (3) isolated coronary arteries mounted in isometric wire myographs. We tested Na‐butyrate added to injection solutions or physiological buffers and compared its effects with equimolar doses of NaCl. Butyrate at plasma concentrations of 0.56 mM increased cardiac output by 48.8±14.9%, stroke volume by 38.5±12.1%, and left ventricular ejection fraction by 39.6±6.2%, and lowered systemic vascular resistance by 33.5±6.4% without affecting blood pressure or heart rate in vivo. In the range between 0.1 and 5 mM, butyrate increased left ventricular systolic pressure by up to 23.7±3.4% in isolated perfused hearts and by 9.4±2.9% following ischemia and reperfusion, while reducing myocardial infarct size by 81.7±16.9%. Butyrate relaxed isolated coronary septal arteries concentration dependently with an EC50=0.57 mM (95% CI, 0.23–1.44). Conclusions We conclude that butyrate elevates cardiac output through mechanisms involving increased cardiac contractility and vasorelaxation. This effect of butyrate was not associated with adverse myocardial injury in damaged hearts exposed to ischemia and reperfusion.